Switchable Surfactant-Assisted Carbon Nanotube Coatings: Innovation through pH Shift - Sanchís, Carlos; Ruiz-Rosas, Ramiro; Berenguer-Murcia, Ángel; Morallón, Emilia; Cazorla-Amorós, Diego (Frontiers in Materials, 2015)
The inner surface of fused silica capillaries has been coated with a dense/homogeneous coating of commercial multi-wall carbon nanotubes (MWCNTs) using a stable ink as deposit precursor. Solubilization of the MWCNTs was achieved in water/ethanol/dimethylformamide by the action of a surfactant which can switch between a neutral or an ionic form depending on the pH of the medium, which thus becomes the driving force for the entire deposition process. Careful control of the experimental conditions have allowed us to selectively deposit CNTs on the inner surface of insulating silica capillaries by a simple, reproducible, and easily adaptable method.